Pengaruh Digital Marketing Dan Digital Service Terhadap Kinerja UMKM : Studi Pada Wirausaha Wanita Desa Sirah Pulau Kecamatan Merapi Timur Lahat - Rosita, Dewi; Antoni, Darius; Samsuddin, Harun (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
The research conducted by the author aims to determine and analyze the influence of digital marketing and digital services individually and together on the performance of MSMEs of female entrepreneurs in Sirah Pulau Village, Merapi Timur District, Lahat. The research method used in this study is quantitative, using a questionnaire distributed to respondents. Data quality testing using validity tests, reliability tests, and classical assumption tests with normality test formulas, heteroscedasticity tests, and multicollinearity tests. The analysis used is descriptive analysis and inferential analysis using statistical calculations with multiple regression formulas, partial tests, simultaneous tests and coefficients of determination. The results of the discussion obtained digital marketing has a significant effect on the performance of MSMEs in Women Entrepreneurs in Sirah Pulau Village, Merapi Timur District, Lahat. Digital service has a substantial effect on the performance of MSMEs in Women Entrepreneurs in Sirah Pulau Village, Merapi Timur. District, Lahat. Digital marketing and digital services significantly affect the performance of MSMEs in Women Entrepreneurs in Sirah Pulau Village, Merapi Timur District, Lahat.